What happens when a marginalized village gets water? - Adhikari, Aashika; Shrestha, Shisher; Karki, Darshan; Khadka, Manohara; Niroula, Aayush (International Water Management Institute, 2025)
In the hills of Sindhupalchowk in Nepal, a newly installed solar lift system carries water uphill to reach the fields and people of a highly marginalized community, bringing relief from scarcity, reducing women’s daily burdens and improving livelihoods.